Ranking the Factors that Influence the Construction Project Success: the Jordanian Perspective - A. Bakr, Ghanim; ., . (International Journal of Engineering and Technology, 2018)
Project success is what must be done for the project to be acceptable to the client, stakeholders and end-users who will be affected by the project. The study of project success and the critical success factors (CSFs) are the means adopted to improve the effectiveness of project.This research is conducted in an effort to identify which factors influence the success of project accomplishment in Jordan. This study has selected, through an extensive literature review and interviews, (83) factors categorized into (7) main groups that the questionnaire respondents were required to score. The responses from 66 professionals with an average of 15 years of experience in different types of construction projects in Jordan were collected and analyzed using SPSS and the most important factors for success for various success criteria are presented depending on the relative importance index to rank the categories. The research revealed the significant groups of factors are: factors related to Client , factors related to Contractorâ€™s, factors related to Project Manager (PM), and factors related to Project management. In addition the top ten sub factors are: Assertion of the client towards short time of the project, availability of skilled labor, Assertion of the client towards high level of the quality, capability of the client in taking risk, previous experience of the PM in similar projects, previous experience of the contractor in similar projects, decision making by the client/ the clientâ€™s representative at the right time, assertion of client towards low cost of project, experience in project management in previous projects, and flow of the information among parties. The findings of this study might be useful to construction project participants in taking decisions leading to successful finishing of construction projects in Jordan.Â
Keywords: Construction projects; Critical success factors; Jordan; project success.